The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fmicb.2016.01201
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of lng Mutations on LngA Expression, Processing, and CS21 Assembly in Enterotoxigenic Escherichia coli E9034A

Abstract: Enterotoxigenic Escherichia coli (ETEC) is a major cause of morbidity in children under 5 years of age in low- and middle-income countries and a leading cause of traveler's diarrhea worldwide. The ability of ETEC to colonize the intestinal epithelium is mediated by fimbrial adhesins, such as CS21 (Longus). This adhesin is a type IVb pilus involved in adherence to intestinal cells in vitro and bacterial self-aggregation. Fourteen open reading frames have been proposed to be involved in CS21 assembly, hitherto o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
1
11
1
Order By: Relevance
“…The role of the single minor pilin in initiating pilus assembly was shown previously in the CFA/III and Longus T4b pilus systems of ETEC [98, 99, 108], which are closely related to V . cholerae TCP in sequence, structure, gene synteny and pilus functions [98, 109].…”
Section: Discussionmentioning
confidence: 68%
“…The role of the single minor pilin in initiating pilus assembly was shown previously in the CFA/III and Longus T4b pilus systems of ETEC [98, 99, 108], which are closely related to V . cholerae TCP in sequence, structure, gene synteny and pilus functions [98, 109].…”
Section: Discussionmentioning
confidence: 68%
“…The crystal structure of CofB in complex with a CofJ N-terminal 24-residue synthetic peptide revealed an unprecedented binding mode, by which the peptide is deeply embedded into the expected GalNAc-binding pocket typically conserved at the trimeric interface of the H-type lectin family ( 25 ). This finding provides a conceptual advance in T4P biology, wherein T4bP anchors the secreted protein at the pilus tip for pathogenesis, as well as a plausible answer for the currently debated association state—either monomeric or trimeric—of the type IVb minor pilin in action ( 24 , 32 34 ), based on the evidence that the trimeric association of CofB is prerequisite for its stable interaction with CofJ ( 32 35 ).…”
Section: Discussionmentioning
confidence: 88%
“…4 A and B ). The presence of an aromatic patch is commonly observed in PFTs and might act as a multivalent lipid-binding site that recognizes lipid head groups of the cell membrane ( 39 41 ), and CofJ reportedly can bind lipid vesicles as well as epithelial cells, such as HeLa and Caco-2 ( 34 ). The lipid-binding nature of CofJ provides advantages for the bacteria by reserving the preferential adhesion spot for initial and/or future attachment to the epithelium as well as in competing with other bacterial species, including commensal species, for subsequent microcolony formation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, due to the LAB-associated fermented foods, the gut microbiota can also be altered in a positive manner and such foods can thereby assist in the resolution of IBD [ 30 , 31 ]. It has been suggested that fermented dairy products have the ability to positively modulate the gut microbiota, either by stimulating the proliferation of beneficial microbes and/or by introducing novel species into the gut [ 32 , 33 , 34 ]. Other investigators have studied the hypocholesteremic and anti-cancer properties of these LAB-associated fermented as well as non-fermented milks [ 35 ].…”
Section: Introductionmentioning
confidence: 99%